Andre Gunder Frank and global development : visions, remembrances and explorations - Manning, Patrick; Gills, Barry K. (London ; New York : Routledge, 2011)
The book focuses on the ideas and influence of Andre Gunder Frank, one of the founding figures and leading analysis of political economy at the global level. . The shifting currents of the world economy and the accompanying controversies , advances and regressions in the understanding of global patterns in the present and the past are all examined in this text. It provides a comprehensive overview of the legacy of Frank's work and takes stock of the recnt and expected developments in global and historical analysis of polical economy.
Includes bibliographical references and index.
opc 30/04/13
Loans
Keywords: Frank, Andre Gunder; Globalization; Global development; International economic relations; Developing countries